Ectogenesis and a right to the death of the prenatal human being: A reply to Räsänen. (25th September 2018) - Kaczor, Christopher
Abstract: Both many critics of abortion and many defenders of abortion have suggested that artificial wombs could end the abortion debate. If the fetus is removed from the uterus, women have an end to an unwanted pregnancy. If the living fetus is then put in an artificial uterus for ectogenesis, there is no termination of the life of the fetus. Joona Räsänen challenges this view in his article, Ectogenesis, abortion and a right to the death of the fetus . Räsänen provides three arguments for a right to secure the death of the human being in utero, namely the 'right not to become a biological parent argument', the 'right to genetic privacy argument', and the 'right to property argument'. This article critiques these three arguments for a right to the death of the fetus.